2010
DOI: 10.1016/j.bone.2009.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of bone loss during 56 days of strict bed rest by side-alternating resistive vibration exercise

Abstract: Bed rest is a recognized model for muscle atrophy and bone loss in space flight and in clinical medicine. We hypothesized that whole body vibration in combination with resistive exercise (RVE) would be an effective countermeasure. Twenty healthy male volunteers underwent horizontal bed rest for 56 days and were randomly assigned either to a group that performed RVE 11 times per week or to a group that underwent bed rest only (Ctrl). Bone mineral content (BMC) was assessed by peripheral quantitative computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
114
3
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(132 citation statements)
references
References 53 publications
10
114
3
5
Order By: Relevance
“…spine, pelvis and legs) [1][2][3]. Evidence [4,5] from bed rest studies, a methodology commonly used to simulate the effects of spaceflight [6], suggests that exercise countermeasures that include highload resistive exercise for the lower limbs and spine would be more effective in reducing bone loss in spaceflight than low load/low impact endurance exercise [1,7,8]. This suggestion corresponds to findings from animal studies [9,10] that loading of bone with larger forces (such as during resistance exercise), leading to greater bone strain [11], generates a greater stimulus for osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…spine, pelvis and legs) [1][2][3]. Evidence [4,5] from bed rest studies, a methodology commonly used to simulate the effects of spaceflight [6], suggests that exercise countermeasures that include highload resistive exercise for the lower limbs and spine would be more effective in reducing bone loss in spaceflight than low load/low impact endurance exercise [1,7,8]. This suggestion corresponds to findings from animal studies [9,10] that loading of bone with larger forces (such as during resistance exercise), leading to greater bone strain [11], generates a greater stimulus for osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work in the 1st Berlin Bed Rest Study [5,21] has shown that RVE can reduce bone loss during prolonged bed rest. Whilst animal studies may strongly suggest that this countermeasure would be more effective than high-load resistance exercise alone (RE), evidence in support of this hypothesis in humans is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…There is little evidence, however, on whether there is a sex difference in rates of bone loss with unloading or in the rate or magnitude of recovery therefrom. While the effects of bed rest on BMD and/or bone metabolism have been examined separately in men 13,14 and in women, 15,16,17 there have been no human studies that have been statistically powered to make direct sex comparisons. In one 17-week bed rest study that included both men (n = 13) and women (n = 5) at one of 10 sites measured (calcaneus), bone loss was markedly less in women than men.…”
Section: Time Course and Magnitude Of Response: Bonementioning
confidence: 99%
“…6 However, the dual energy x-ray absorptiometry-assessed total hip BMD for women in a 60-day bed rest study 17 revealed a substantial loss at that site, whereas men in a similar study did not have a decrease in total hip bone mineral content. 13 Volumetric BMD and bone geometry of tibial cancellous and cortical compartments have been evaluated after prolonged bed rest using peripheral quantitative computed tomography (pQCT) in men 13,15 and high-resolution pQCT in women. 16 The small gender differences observed in the bone loss rates at those tibial sites are within the reported precision for these pQCT variables.…”
Section: Time Course and Magnitude Of Response: Bonementioning
confidence: 99%
“…The latter refers to the evidence that HF mechanical loading improves the bone's mechanical properties, thereby promoting its properties to withstand the physiological demands [2]. This makes HF mechanical loading a potent nonpharmacological intervention for osteoporosis, fracture healing and beyond [2,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%